Production of a new anti-M monoclonal reagent using human hybridoma technology . - Boonhai, S.; Aiemumpron, K.; Tingtoy , U. (Chulalongkorn Medical Journal, 2023)
Background : The standard reagent for M-antigen blood group testing form the National Blood Centre is currently ineffective as it is rabbit polyclonal antibodies which have low potency and specificity. Objectives : To develop new high efficacy monoclonal anti-M antibodies. Materials and Methods : By using a fusion technique, anti-M secreted B-lymphocytes were fused with the same species of myeloma cells (JMS-3) to generate anti-M secreted hybridoma cells. Subsequently, monoclonal anti-M antibodies were individually harvested from each hybridoma cell culture supernatant. In order to determine the antibodies’ efficacy, compared with the standard polyclonal anti-M antibodies from the National Blood Centre and commercial monoclonal anti-M antibodies. Results : The results showed that the newly-developed monoclonal anti-M antibodies (Clone 1F9) have higher potency than the standard polyclonal anti-M antibodies from the National Blood Centre, while it was equivalent to or having higher potency than the commercial ones. From slide avidity testing, new-developed monoclonal anti-M antibodies (Clone 1F9) reacted with M-antigen positive RBC within 1- 2 seconds, However, there is no difference among the newly developed monoclonal antibodies and other two of standard reagents. As for specificity testing, 800 M-antigen positive RBC samples and 400 M-antigen negative RBC samples were tested against monoclonal anti-M antibodies (Clone 1F9). The result showed that monoclonal anti-M antibodies (Clone 1F9) specifically reacted with M-antigen positive RBC (100%); concurrently, there was no detectable reaction in M-antigen negative RBC (100%) and papainized identification panel cells (Lot 58040). In term of antibodies stability, monoclonal anti-M antibodies (Clone 1F9) were stored at 4°C for longer than 18 months and yet there was no reduction of the antibodies potency. An adequate pH range for antibodies reaction is very wide, from pH 5 to pH 9, which is similar to that of the standard reagents. Regarding the effect of temperature on there action of the antibodies, it was found that the human monoclonal anti-M (clone 1F9) can react well at low temperature, and the reaction occurs at 4°C and 20 - 25°C (room temperature), far better than the temperature of 37°C. Conclusion : The newly developed monoclonal anti-M antibodies (Clone 1F9) show high potency, avidity, specificity, and stability with a wide range of pH and low temperature usages. Thus, this might suggestively be a new reagent for human blood group testing in laboratory.